Penerapan Perencanaan Pajak Pertambahan Nilai Sebagai Bentuk Efisiensi Pajak Pada Klien KJA XYZ - Yuniar, Vidya Dwi; Suryaningrum, Diah Hari (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research examines the implementation of tax planning for Value Added Tax (VAT) at the XYZ Accounting Firm (KJA) to enhance tax efficiency. In Indonesia, the self-assessment tax system requires taxpayers to calculate and report their own taxes, prompting businesses to seek strategies to minimize tax burdens and maximize profits. VAT, as a consumption-based tax, represents a significant source of government revenue. KJA XYZ supports its clients in VAT planning through measures such as utilizing automated Excel tools and providing education on tax regulations. Despite these efforts, challenges such as invoice data discrepancies have been identified. To address these issues, it is recommended that KJA XYZ further develop its automation systems and enhance communication with clients. The findings of this study indicate that effective VAT planning contributes positively to clients’ tax efficiency.